Determination of Tetracycline by Microdroplet Hydrodynamic Adsorptive Voltammetry Using a Multiwalled Carbon Nanotube Paste Rotating Disk Electrode. (3rd May 2019) - Sultana, Ayesha; Sazawa, Kazuto; Islam, Md. Saiful; Sugawara, Kazuharu; Kuramitz, Hideki
Abstract: A novel and simple method is proposed for the determination of tetracycline by adsorptive voltammetry in a droplet using a carbon nanotube paste rotating disk electrode (CNTP-RDE). An enhanced electrochemical oxidation response of tetracycline was observed in pH 8.2 supporting electrolyte by the addition of a long-chain cationic surfactant, such as benzyldimethyltetradecylammonium chloride (zephiramine). Under the optimized experimental conditions, the calibration curve was linear across a tetracycline concentration range from 1.0 × 10 −7 to 2.0 × 10 −6 M. The limit of detection and sensitivity were 4.0 × 10 −8 M and 0.9358 A M −1, respectively. This method was successfully employed for the determination of tetracycline in milk samples.